Characterisation and effect of polymer network deformation in reverse-mode polymer-stabilised cholesteric texture. Issue 3 (19th February 2017) - Lu, Hongbo; Chu, Yutian; Jing, Shuaicheng; Zhang, Guobing; Hu, Juntao; Lv, Guoqiang; Qiu, Longzhen
ABSTRACT: In reverse-mode polymer-stabilised cholesteric texture (PSCT), the dynamic response is derived from local director reorientation governed by dielectric coupling effect/self-assembly and polymer network deformation. A double exponential rise/decay model is proposed to investigate the underlying physical mechanisms. Through simulation of the transient rise and decay processes, the polymer network deformation in PSCT can be quantitatively evaluated. Less deformation and faster restoration speed of the polymer network can suppress hysteresis. These results provide useful guidelines for future PSCT fabrication and performance optimisation. GRAPHICAL ABSTRACT: